Carnivalesque, creativity, and the becomings: a critical assessment of the politics of resistance in Batman: Arkham Asylum - Kodencheri, Anupama; Chithra, Gandhapodi K. (Creativity Studies, 2024)
There is a growing academic interest in respect for critical game studies from the domains such as cultural studies, literature, ludology, and gender studies. However, the research done on videogames from the perspective of the political discourse is not broad enough. Rocksteady Studios’ Batman: Arkham Asylum (2009, director Sefton Hill) is a franchise that has redefined the superhero videogame genre. Although previous Batman transmedia adaptations would usually portray Gotham City as the prime location to narrate the story from the perspective of Batman, the videogame utilizes the carceral setting of Batman to subvert the traditional narratives and makes it completely a Joker’s (character) game. Therefore, this version of storytelling carries a character with a more nuanced demeanor and a setting with socio-political influence. The current paper examines the underlying structural inequality present in Batman using Giorgio Agamben’s bare life theory and the subsequent discourse of resistance using the theoretical framework of Mikhail Bakhtin. The analysis reveals the various carnivalesque elements present in the game and illustrates how the game takes advantage of them to mount an attack against the bare life status of the antagonists that are usually seen in Batman transmedia universe. Furthermore, the paper elaborates on the posthuman traits of Joker’s becoming through a Gilles Deleuze-inspired perspective.